The associations between personality functioning (Criterion A) and pathological personality traits (Criterion B) in the alternative model for personality disorders in DSM-5: a meta-analysis - Thimm, Jens C. (Frontiers in Psychiatry, 2025)
IntroductionThe Alternative Model for Personality Disorders in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5 AMPD) requires the assessment of personality functioning (Criterion A), using the Level of Personality Functioning Scale (LPFS), and the presence of pathological personality traits (Criterion B), operationalized with the Personality Inventory for DSM-5 (PID-5). Several studies have investigated the associations between the LPFS and the PID-5 personality traits as well as the normal-range personality traits of the Five-Factor Model (FFM) of personality. The goal of the present study was to meta-analytically integrate the findings of these studies to examine the extent to which the LPFS is related to the PID-5 and FFM traits.MethodsA systematic literature search was conducted in the databases PsycINFO, Medline, Embase, and Web of Science for studies providing information about the correlations of the measures of the LPFS with versions of the PID-5 and/or measures of the FFM in adult samples. The bivariate correlations of scales measuring the LPFS with the measures of the PID-5 and FFM traits were meta-analytically pooled.ResultsData from 44 studies and 47 independent samples were identified and used in the analyses. The results showed medium-to-large weighted average correlations between the LPFS total score and the PID-5 traits, ranging from.44 (antagonism) to.64 (detachment). Overall, lower correlations were found between the LPFS and the FFM traits.DiscussionTentative explanations for these associations are discussed, and suggestions to reduce them—including potential modifications to one or both criteria—are presented.Systematic review registrationhttps://osf.io/49rs7, identifier doi.org/10.17605/OSF.IO/49RS7.